2023
DOI: 10.1371/journal.pone.0283637
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile, their antibiotic susceptibility pattern, and associated factors of urinary tract infections in children at Hiwot Fana Specialized University Hospital, Eastern Ethiopia

Abstract: Background Urinary tract infections (UTIs) are common pediatric infections and contribute to high morbidity and mortality. At present, the antimicrobial resistance emergency has quadrupled worldwide and poses a serious threat to the treatment of patients. However, there have been few studies on UTIs in children in Ethiopia, particularly in the east. Objective This study aimed to assess the bacterial profile of urinary tract infections, their susceptibility to antimicrobial agents, and associated factors in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Previous similar studies have also reported a link between bacterial infections in urine and factors such as residing in rural areas, being uncircumcised, and experiencing frequent urination, which could be more prevalent in older age groups. Additionally, the frequency of resistance in urinary tract infections is higher due to patients often receiving prescribed antibiotics and self-administering them without supervision, particularly in regions where self-medication practices are common [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous similar studies have also reported a link between bacterial infections in urine and factors such as residing in rural areas, being uncircumcised, and experiencing frequent urination, which could be more prevalent in older age groups. Additionally, the frequency of resistance in urinary tract infections is higher due to patients often receiving prescribed antibiotics and self-administering them without supervision, particularly in regions where self-medication practices are common [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Geographically, the studies were distributed across various regions of Ethiopia, with eight conducted in the Amhara region [ 26 33 ], three in Oromia [ 34 36 ], three in SNNPR [ 37 39 ], four in Addis Ababa [ 40 43 ], and one in Harari [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Indonesia reported that circumcision was associated with a decreased incidence of UTI in children [ 32 ]. Additionally, a study conducted in Ethiopia found that uncircumcised male children have a higher risk of acquiring UTI compared to those who are circumcised [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The commonly reported factors include female gender, poor hygiene, poverty, malnutrition, and recurrent infections [ 11 ]. Other predisposing factors include lower age, uncircumcision in males, genitourinary anomalies, indwelling urinary catheters, and previous antibiotic use [ 12 , 13 ]. Urine culture is rarely performed as part of patient management in rural areas with inadequate diagnostic resources.…”
Section: Introductionmentioning
confidence: 99%